Virgin Widows - Gu, Hua (University of Hawaii Press, 1996)
Virgin Widows is a poignant and disquieting novel that unfolds the stories of two women whose lives, despite being separated by nearly a century, reveal a disturbing similarity. First published in China in 1985, it appears now in English for the first time